PERJUANGAN PEREMPUAN DALAM KUMPULAN CERPEN NADIRA KARYA LEILA S. CHUDORI: KAJIAN FEMINISME - Syainit, Rahma Aulia; Hayati, Yenni; Nasution, Muhammad Ismail (Jurnal Bahasa dan Sastra, 2018)
The object of this study was a collection of short stories Nadira written by Leila S. Chudori. This research aims to describe (1) women's struggle, and (2) ideas of feminism in a collection of short stories Nadira by Leila S. Chudori. Theoritical studies used in this research are: (1) the definition of short stories and (2) fictional structure, consists of (a) intrinsic element, and (b) extrinsic elements, (3) fictional analysis approach, and (4) the essence of feminism. The study used feminist literary criticism. Based on the story of this collection of short stories, another study used theory of socialist feminism. Feminism refers to a thought or ideology that want justice and gender equality. Because of these ideals, then feminism is regarded as an ideology of women's liberation. While socialist feminism statesÂ  the cause of oppression in women is capitalism and patriarchy. Feminism literary criticism means â€œreading as womanâ€. This feminism literary criticism analysis was conducted using feminism approach. This study will examine the women's struggles in the social, economic, educational, and politicalÂ  contained in this collection of short stories.Keywords: women, feminism, feminist- socialist, feminism ideasÂ